2022
DOI: 10.1017/jfm.2022.369
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction on a transonic airfoil

Abstract: Flow control for turbulent skin-friction drag reduction is applied to a transonic airfoil to improve its aerodynamic performance. The study is based on direct numerical simulations (with up to 1.8 billion cells) of the compressible turbulent flow around a supercritical airfoil, at Reynolds and Mach numbers of $Re_\infty = 3 \times 10^{5}$ and $M_\infty =0.7$ . Control via spanwise forcing is applied over a fraction of the suction side of the airfoil. Besid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…viscous) drag (Akhavan, Jung & Mangiavacchi 1993;Gatti & Quadrio 2013Ricco, Skote & Leschziner 2021), suggesting continued drag reduction, if implemented on a surface with varying roughness properties over time. Notably, the same strategy has also been found to yield significant drag reduction in the scenario of a transonic flow over a wing (Quadrio et al 2022), indicating success of this strategy across a broad range of flows.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…viscous) drag (Akhavan, Jung & Mangiavacchi 1993;Gatti & Quadrio 2013Ricco, Skote & Leschziner 2021), suggesting continued drag reduction, if implemented on a surface with varying roughness properties over time. Notably, the same strategy has also been found to yield significant drag reduction in the scenario of a transonic flow over a wing (Quadrio et al 2022), indicating success of this strategy across a broad range of flows.…”
Section: Introductionmentioning
confidence: 82%
“…Notably, the same strategy has also been found to yield significant drag reduction in the scenario of a transonic flow over a wing (Quadrio et al. 2022), indicating success of this strategy across a broad range of flows.…”
Section: Introductionmentioning
confidence: 86%
“…In Figure 9, the pressure coefficient and skin friction coefficient show how the shock wave was stronger and moved downstream with the riblets installed also causing a shock-induced separation. A very recent DNS computation [41] confirmed the effect of the reduced skin friction on the shock wave strength and position due to a drag reduction device. In the next sections, the effect of riblets on the form drag and shock wave of a full aircraft configuration will be shown.…”
Section: Effect Of Riblets On Form Drag and Shock Wavementioning
confidence: 87%
“…The StTW, introduced by Quadrio, Ricco & Viotti (2009), are interesting owing mainly to their good energetic performance, which is preserved at high Reynolds numbers (Gatti & Quadrio 2016). The StTW are effective even in compressible and supersonic flows (Ruby & Foysi 2022;Gattere et al 2024), and have been demonstrated to affect favourably the aerodynamic drag of a three-dimensional body (Banchetti, Luchini & Quadrio 2020), up to the point that an actuation over a limited portion of the wing of an airplane in transonic flight reduces the total drag of the aircraft by nearly 10 % at a negligible energy cost (Quadrio et al 2022).…”
Section: Introductionmentioning
confidence: 99%